2010
DOI: 10.1590/s0104-12902010000600004
|View full text |Cite
|
Sign up to set email alerts
|

Perfis de Vulnerabilidade Feminina ao HIV/aids em Belo Horizonte e Recife: comparando brancas e negras

Abstract: Objetivo: Delinear e comparar os perfis das mulheres brancas e negras entre 18 e 59 anos, residentes em Belo Horizonte e Recife, enfocando características sociodemográficas e de conhecimento, além de atitudes em relação ao HIV/aids. Métodos: Os dados são oriundos da pesquisa amostral SRSR -Saúde Reprodutiva, Sexualidade e Raça/Cor, conduzida pelo Cedeplar/UFMG em 2002 e única desta natureza com representatividade municipal. O método utilizado foi o Grade of Membership (GoM), a partir do qual foram gerados quat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
6
1
6
Order By: Relevance
“…In this study the population consisted of 67% white, 9% black, 23% mixed and 1% Asian. A different result was found in literature, which reveals greater vulnerability of black to HIV/AIDS in Brazil (16) . In the study conducted in the United States of America, that estimated the incidence of HIV between 2006 and 2009, it was observed that the only group that showed an increase in the incidence rate was the young black males who had sexual intercourse with other men (19) .…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In this study the population consisted of 67% white, 9% black, 23% mixed and 1% Asian. A different result was found in literature, which reveals greater vulnerability of black to HIV/AIDS in Brazil (16) . In the study conducted in the United States of America, that estimated the incidence of HIV between 2006 and 2009, it was observed that the only group that showed an increase in the incidence rate was the young black males who had sexual intercourse with other men (19) .…”
Section: Discussioncontrasting
confidence: 62%
“…However, it is currently noticeable the increase of AIDS cases among women (16) who, in general, have lower income, a more susceptible health and succumb to this disease faster than men (17) . The improved quality of life with access to health services, medication, better nutrition, leisure and general wellbeing conditions, as well as recent advances of the pharmaceutical industry and the medicine, allow the extension of an active sex life and, in association with the demystification of the gender, make the elderly more vulnerable to sexually transmitted infections, among them, the HIV/AIDS (18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazilian ethnographic experts have illuminated, for example, power exerted over low-SES women commonly related to condom negotiations and intimate-partner violence (23). In Brazil, higher educational attainment was associated with lower adolescent and unintended pregnancy (15,55), and more con dence in enforcing condom use (25), resulting in higher condom practice (26,46). As noted, condom practice and pregnancy prevention remained of primary interest when analyzing the Zika epidemic, given the disease sexual transmission.…”
Section: Individual-levelmentioning
confidence: 99%
“…There are several barriers to contraceptive implementation, such as lack of access and high costs (13,14), inconsistent use (15), methods with high failure rate and lack of access to medical care (16). These vulnerabilities add to intimate-partner violence, women's powerlessness to negotiate condom use and other gender norms in partner interaction (17)(18)(19)(20)(21)(22)(23), which could prevent both pregnancy and sexual transmission of Zika, especially among the less educated (18,(24)(25)(26). Women who lack reproductive rights are among the poorest and less educated in the country, and oftentimes, live in the least developed areas of the country.…”
Section: Introductionmentioning
confidence: 99%